PENGGUNAAN MODEL SCS-CN UNTUK MENGESTIMASI RUNOFF PADA SUB DAS TUKAD NYULING-BALI - , YULI MALINA; , Dr. Ir. Ambar Kusumandari, MES. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Runoff data is very important because it can be used to monitor the health of watershed. But in fact, to obtain the data is not easy because of the lack of river flow monitoring equipment in the form of SPAS. Therefore where a model that can be used to predict runoff is needed. SCS-CN is one of the simplest model and is often used to resolve the issue. The research was carried out at Tukad Nyuling sub watershed. The research objectives are: calculate runoff with SCS-CN method, determine the level of accuracy of SCS-CN method in predicting runoff, knowing linkages the rainfall with runoff and knowing linkages the land use composition with runoff at Tukad Nyuling sub watershed. The result showed that the rainfall between 10,5 mm and 55 mm generate runoff that range 0,02 mm to 7,76 mm. Goodness of fit test based on d.b. 12 if the significance level Î± = 0,05 calculate yield X2 of 142,326 and X2 Table of 21,026. Calculate X2 > X2 Table so the conclusion Ho is rejected (runoff method result do not fit with the result of direct runoff measurements). In order word SCS-CN method is not feasible to use. Methods must be calibrated to provide a more accurate/close to accurate so that it can be used. Further daily rainfall or rainfall five days earlier known equally affect the runoff. With the land use is dominated by 44,46% moor and forest area there is only 12,31% but has performed well Tukad Nyuling sub watersheds.